Telly can make science pants. - Fong, Kevin (Times Higher Education Supplement, 2006)
This article describes the author's experience of auditioning for a television science program in Great Britain. He was introduced to a co-presenter who does not have a background in science. The author learned that collaborating with the media is not a good idea. Contrary to popular belief, science professionals will have plenty to lose, including their self-respect.